2004
DOI: 10.1016/j.jvs.2003.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Disease progression in contralateral carotid artery is common after endarterectomy

Abstract: After CEA, we identified an 8.3% annual rate of progression of contralateral carotid artery stenosis and a 4.4% annual rate of progression to severe stenosis or occlusion. Baseline contralateral stenosis was significantly predictive of progression to severe stenosis or occlusion. Clinical and demographic factors were not helpful in predicting which patients would have disease progression. These data may help in assessing the cost effectiveness of duplex scanning surveillance after CEA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
36
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 26 publications
(22 reference statements)
8
36
0
3
Order By: Relevance
“…11,12,[32][33][34][35][36][37] In the present study, 22.1% of patients experienced progression of ICS during 36.2 months after contralateral CAS, which is consistent with observations from previous reports. Several studies have described risk factors for ICS progression, including female sex, black race, baseline ICS 50% or greater, systolic blood pressure Ͼ160 mm Hg, CAD, smoking, low ankle-brachial pressure index, and echolucent plaques.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…11,12,[32][33][34][35][36][37] In the present study, 22.1% of patients experienced progression of ICS during 36.2 months after contralateral CAS, which is consistent with observations from previous reports. Several studies have described risk factors for ICS progression, including female sex, black race, baseline ICS 50% or greater, systolic blood pressure Ͼ160 mm Hg, CAD, smoking, low ankle-brachial pressure index, and echolucent plaques.…”
Section: Discussionsupporting
confidence: 90%
“…[10][11][12][13] Patients who undergo CAS are given antiplatelet agents in addition to other antiatherosclerotic medications. Antiplatelet agents are effective for the reduction of stent thrombosis after CAS and for the reduction of the risk of vascular events in other arterial beds, which provides a rationale for their long-term use in these patients.…”
mentioning
confidence: 99%
“…[16][17][18] Some natural history studies of populations with asymptomatic carotid stenosis have investigated progression of stenosis in the artery contralateral to CEA, but the natural history of severe stenosis is not usually available because so many patients with suitable (≥60% to 70%) stenosis undergo prophylactic endarterectomy leaving only some, who may be less fit for surgery, for long-term follow-up. 7,[19][20][21][22] In 1 natural history study of progression of stenosis in carotid artery disease, Lewis found there was a significantly higher risk of stroke or death (risk ratio, 3.0; 95% confidence interval, 1.3-6.7) once stenosis reached 80% stenosis or more. 23 Ballotta 7 followed up carotid stenosis contralateral to CEA and found that progression from moderate (50% to 69%) to severe (70% to 99%) stenosis was strongly associated with transient ischemic attack or stroke, >80% of the neurological events in this study occurring in this group of patients.…”
Section: Strokementioning
confidence: 99%
“…48,60 Numerous studies have analyzed the rate and severity of carotid artery occlusive progression, but the results show considerable differences. 11,25,49 Table 2 summarizes the results of some of these studies.…”
Section: Progression Of Carotid Artery Occlusive Diseasementioning
confidence: 99%
“…7,23,37,48 Carotid artery disease progression appears to be associated with diabetes, smoking, hypertension, and, in patients with more severe stenosis, heterogeneous plaque and contralateral disease. 6,11,37,48,60 Moreover, the severity of the stenosis is a risk factor for progression, with moderate stenosis being 5-fold more likely to progress than mild or no stenosis.…”
Section: Progression Of Carotid Artery Occlusive Diseasementioning
confidence: 99%